2. SYSTEMATIC REVIEW OF THE PREVALENCE OF DRUG INTERACTIONS IN HOSPITAL SETTINGS FOR THE PERIOD OF 2022-2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The systematic review aims to identify common pairs of adverse drug-drug interactions (DDIs) in hospital treatment based on published research findings worldwide from 2022 to 2023.Materials and methods: Utilize specific command syntax to search and filter on PubMed for full-text studies in English that focus on the DDI rates, published during the period 2022-2023.Results: A total of 393 different DDI pairs were recorded from 20 articles that met the study inclusion criteria. The most frequent DDI pair was lorazepam + olanzapine (55.5%). Ritonavir was the most frequently implicated drug, involved in 24 out of 393 DDI pairs (6.1%). Eleven DDI pairs were listed in the "Issuance of the list of contraindicated drug interactions in clinical practice at healthcare facilities" (Decision No. 5948/QD-BYT). Among these, erythromycin + fluconazole and ceftriaxone + calcium gluconate were the most commonly prescribed, with the rates of 33.6% and 25.0%, respectively.Conclusions: The prescription of interacting drugs remains a critical concern in clinical practice. Many DDI pairs observed in hospitals worldwide are not included in Decision No. 5948/QD- BYT (2021). Therefore, healthcare professionals need to regularly update their knowledge of drug interations from various sources to optimize decision-making for the prevention and resolution of DDIs, thereby ensuring patient safety during treatment.
Keywords: Drug-drug interactions, Decision No. 5948/QD-BYT, systematic review, Lexicomp.